2016
DOI: 10.1097/iae.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Central Serous Chorioretinopathy Treated With Mineralocorticoid Antagonists

Abstract: Mineralocorticoid antagonists may improve best-corrected visual acuity and decrease subretinal fluid in patients with central serous chorioretinopathy, but do not affect the choroidal or macular thickness. This pilot study demonstrates that mineralocorticoid receptor antagonists may be effective in treating central serous chorioretinopathy but warrants consideration for future research within a randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 23 publications
2
40
2
3
Order By: Relevance
“…Our data compare favorably to the study of Chin et al [12], in which only half of the patients had a positive treatment effect with MR antagonists, but the patients who did best in their study were in the treatment-naïve subset, which represents all of the patients in our study. While Ghadiali et al [13] observed nonstatistically significant improvements in vision in their study, their sample was markedly different from ours because only 12 of 23 had subretinal fluid in their sample, whereas all of our patients had subretinal fluid. Salz et al [15] demonstrated that at 3 months, 64% of patients had complete resolution of subretinal fluid under treatment, which compares favorably to our rate of 58.3% having complete resolution at 2 months.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Our data compare favorably to the study of Chin et al [12], in which only half of the patients had a positive treatment effect with MR antagonists, but the patients who did best in their study were in the treatment-naïve subset, which represents all of the patients in our study. While Ghadiali et al [13] observed nonstatistically significant improvements in vision in their study, their sample was markedly different from ours because only 12 of 23 had subretinal fluid in their sample, whereas all of our patients had subretinal fluid. Salz et al [15] demonstrated that at 3 months, 64% of patients had complete resolution of subretinal fluid under treatment, which compares favorably to our rate of 58.3% having complete resolution at 2 months.…”
Section: Discussioncontrasting
confidence: 49%
“…Other recent studies utilizing MR antagonists in CSCR have corroborated these concerns [12,13,14]. While the present study is unique in its study design comparing two different MR antagonists and an observation arm, it is useful to compare the data to other recent studies.…”
Section: Discussionmentioning
confidence: 57%
“…(13) Todos os grupos avaliados apresentaram melhora significativa no volume de liquido subfoveal, espessura macular, espessura coroidea subfoveal e acuidade visual, com resposta mais lenta nos portadores de CSC apresentando sinais de "calha" e alterações gravitacionais do epitélio pigmentado.…”
Section: ) Bloqueadores Dos Receptores De Mineralocorticoides (Mra)unclassified
“…(2) Alguns critérios para contraindicação ao uso dos MRa são: gestação, insuficiência renal, hepática ou cardíaca, hiperpotassemia, usuários de inibidores da enzima de conversão da angiotensina, drogas anti-inflamatórias não esteroides, lítio e inibidores da CYO3A4. (2,13) 2) Outras Classes de Drogas:…”
Section: ) Bloqueadores Dos Receptores De Mineralocorticoides (Mra)unclassified
“…Recent reports have pointed to new therapeutic applications for SPL (and its active metabolites); for example, it is being increasingly prescribed “off‐label” in ophthalmology for the treatment of central serous chorioretinopathy (Bousquet et al, ; Chin et al, ; Daruich et al, ; Ghadiali, Jung, Yu, Patel, & Yannuzzi, ; Herold, Prause, Wolf, Mayer, & Ulbig, ; Herold, Rist, Priglinger, Ulbig, & Wolf, ; Salehi, Wenick, Law, Evans, & Gehlbach, ; van Dijk et al, ), which involves the accumulation of fluid under the retina and can result in retinal detachment and vision impairment. Other studies have suggested that concomitant administration of MR antagonists might offset glucocorticoid‐induced delays in cutaneous wound healing (Farman et al, ; Maubec et al, ; Nguyen et al, ).…”
Section: Introductionmentioning
confidence: 99%